Preparation method of heat-insulating hydrophobic wood
By combining modified silica aerogel powder with wood, the problems of poor thermal insulation performance and low dimensional stability of wood are solved, and the thermal insulation, hydrophobic and mechanical properties of wood are improved.
Patent Information
- Application Number
- CN202411511917.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-28
AI Technical Summary
The high thermal conductivity of wood leads to poor thermal insulation performance, while its hydrophilicity makes dimensional stability low, requiring a simple, economical and scalable method to improve the thermal insulation and hydrophobicity of wood.
Silica sol is prepared by using silicon source and acid as raw materials, then adding an alkaline solution to prepare the gel and aged, followed by hydrophobic modification and drying to obtain a modified silica aerogel powder, which is added to the wood by vacuum impregnation.
It improves the thermal and sound insulation properties of wood, while enhancing the dimensional temperature and mechanical properties of the material, solving the problem of wood's sensitivity to water.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy conservation and environmental protection, and particularly relates to a method for preparing heat-insulating and hydrophobic wood. Background Art
[0002] Wood is a sustainable material with unique visual properties, friendly to humans and the environment, and widely used in interior decoration and construction. The thermal conductivity of wood is about 0.1 W / (m•K)−1, which is relatively high, and its thermal insulation effect is poor. Further improving its thermal insulation performance is a current research direction. On the other hand, the hydrophilicity of cellulose and hemicellulose, the main chemical components of wood, makes wood sensitive to water, which often leads to low dimensional stability of wood or wood-based products. Therefore, there is an urgent need to find a simple, economical, and industrially scalable method to treat wood to improve its thermal insulation and hydrophobicity.
[0003] CN111185977A discloses a method for producing super-hydrophobic wood, which makes the wood surface hydrophobic by coating a mixed material of polydimethylsiloxane and nano-silica microspheres on the wood surface. If the polydimethylsiloxane and nano-silica microsphere mixed material coated on the wood surface is scratched during cutting or use, its hydrophobic and heat-insulating effects will be affected. At the same time, the thermal conductivity of the nano-silica microspheres is high, and the heat-insulating effect is poor. Summary of the invention
[0004] The invention provides a method for preparing heat-insulating and hydrophobic wood. After the wood is impregnated with modified silica aerogel powder as a hydrophobic material, the wood has good heat-insulating and sound-insulating properties, and can also improve the dimensional temperature resistance of the material and enhance the mechanical properties.
[0005] The technical solution of the present invention is to provide a method for preparing heat-insulating and hydrophobic wood, comprising the following steps: S1, using a silicon source and an acid as raw materials, mixing to prepare a silica sol, then adding an alkaline solution to prepare a gel and aging; S2, the aged gel is crushed, hexamethyldisiloxane and hydrochloric acid are added for hydrophobic modification, and after modification, it is cooled and allowed to stand, the modified waste liquid at the lower layer is discharged, the gel solution at the upper layer is filtered, and dried to obtain modified silica aerogel powder; S3, adding the modified silica aerogel powder obtained in S2 into ethanol and mixing evenly, adding dry wood for vacuum impregnation, and drying after the impregnation to obtain heat-insulating and hydrophobic wood.
[0006] Furthermore, in S1, the silicon source is water glass with a silicon content of 20-30%; the acid is concentrated sulfuric acid with a concentration of 80-98%; water needs to be added during the mixing process, the mass ratio of water glass to water is 1-5:1-5, and the mass ratio of concentrated sulfuric acid to water is 1-5:1-10; after the silicon source, acid and water are mixed, a sol is obtained by dropping and stirring, the dropping time is 10-60 min, and the stirring speed is 100-1000 rpm / min.
[0007] Furthermore, the alkaline solution in S1 is ammonia water with a concentration of 1-10%, and the mass ratio of sol to ammonia water is 1-10:1-5; the pH of the sol is adjusted to 3-8 by ammonia water; the temperature of the gel heating aging is 40-80°C; and the aging time is 1-24h.
[0008] Furthermore, the mass ratio of hydrochloric acid, hexamethyldisiloxane and gel in S2 is 1~5:1~10:1~5; the concentration of hydrochloric acid is 25-35%; the temperature of hydrophobic modification of the gel is 40~80°C; the stirring speed is 100~1000rpm / min; and the modification time is 1~12h.
[0009] Furthermore, the filter cake obtained after filtering the gel solution in the upper layer of S2 is mixed and washed with hexamethyldisiloxane, filtered again, and then dried.
[0010] Furthermore, the drying temperature of the gel in S2 is 70-150°C.
[0011] Furthermore, the mass ratio of the modified silica aerogel powder to ethanol in S3 is 0.001~1:1~5.
[0012] Furthermore, the impregnation vacuum pressure in S3 is 0.01~0.1MPa; the impregnation time is 1~5h; the drying temperature of the wood board is 80~150°C; and the drying time is 1~5h.
[0013] Furthermore, the dipping and drying steps in S3 are cycled 1 to 5 times.
[0014] The invention also relates to the heat-insulating and hydrophobic wood prepared by the method.
[0015] The present invention has the following beneficial effects: The present invention firstly prepares gel from water glass and concentrated sulfuric acid through a sol-gel method, and produces silica aerogel powder through hydrophobic modification and drying. The generated silica aerogel powder has good hydrophobicity and low thermal conductivity, and the process is simple and the cost is low. The silica aerogel powder is then dissolved in anhydrous ethanol and then vacuum impregnated into the wood. The wood compounded with the silica aerogel powder has good thermal insulation and sound insulation properties, and the hydrophobicity of the silica aerogel powder also greatly enhances the dimensional stability of the wood. Moreover, after the silica aerogel powder is immersed in the wood, the tensile strength of the wood is enhanced, so that its mechanical properties are better.
[0016] The wood provided by the invention can well solve the problems of heat insulation, sound insulation and noise reduction, waterproof and moisture-proof for indoor building decoration, and is non-toxic, harmless and environmentally friendly. In addition, after the modified silica aerogel powder is immersed in the wood, it has an effect of enhancing the tensile strength of the wood, making its mechanical properties better. DETAILED DESCRIPTION
[0017] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0018] Example 1 A method for preparing a heat-insulating and hydrophobic wooden board, the specific steps are as follows: Step 1, by weight, dilute 25 parts of water glass with a silicon content of 26wt% in 22 parts of deionized water. Dilute 4.8 parts of concentrated sulfuric acid with a concentration of 98wt% in 19.2 parts of deionized water. Then slowly add the diluted water glass to the diluted sulfuric acid, the addition time is 30min, and the stirring speed is 200rpm / min. After the addition is completed, slowly add 42 parts of ammonia water with a mass concentration of 1% to the silica sol and stir until the pH of the sol is 7 for gelation. Finally, heat the gel to 60°C for aging, the aging time is 24h, and silica gel is obtained.
[0019] Step 2, the aged silica gel is crushed, 30 parts of hydrochloric acid with a concentration of 30wt% and 200 parts of hexamethyldisiloxane are added to carry out hydrophobic modification of the gel, the modification temperature is 60°C, the modification time is 3h, and the stirring speed is 300rpm / min. After the modification is completed and cooled, the modified waste liquid of the lower layer is released, and then the gel solution of the upper layer is filtered to recover the solvent. 200 parts of hexamethyldisiloxane are added to the filtered gel for stirring and cleaning, the cleaning time is 0.5h, the stirring speed during cleaning is 200rpm / min, and the cleaning is left to stand for 1h, and then filtered. The filtered gel is dried at a drying temperature of 120°C and a drying time of 3h to obtain modified silica aerogel powder.
[0020] Step 3: Dissolve 0.05 parts of modified silica aerogel powder in 100 parts of anhydrous ethanol by weight, then soak the dried wood board in the silica aerogel powder ethanol solution, evacuate the soaking container to 0.01 MPa, and then soak for 2 hours. Dry the soaked wood board in an oven at 100° C. for 2 hours to obtain the final product.
[0021] Test Application In test 1, the original wood and the final product were cut into 1cm thick and 20*20cm boards, and their room temperature thermal conductivity was measured by the flat plate heat flow method. The room temperature thermal conductivity of the original wood was 0.11W / (m·K), and the room temperature thermal conductivity of the final product was 0.093W / (m·K). It can be seen that silica aerogel powder has a certain effect on reducing the thermal conductivity of wood.
[0022] Test 2: The original wood and the final product were cut into 1cm thick and 30*15cm boards, and their hydrophobicity was tested with a hydrophobicity meter. The hydrophobicity of the original wood was 92.43% and the hydrophobicity of the final product was 94.17%. It can be seen that silica aerogel powder has a certain improvement on the hydrophobic properties of wood.
[0023] Test three, the original wood and the final product were cut into 1cm thick and 16*5cm boards, and their tensile strength was tested with an electronic universal testing machine. The tensile strength of the original wood was 39.7MPa, while the tensile strength of the final product was 68.6MPa. From this we can see that the silica aerogel powder has a significant improvement in the tensile strength of the wood. This may be because the tiny silica aerogels entered the gaps inside the wood, improving its mechanical properties and thus enhancing the tensile strength.
[0024] Example 2 A method for preparing a heat-insulating and hydrophobic wooden board, the specific steps are as follows: Step 1, by weight, dilute 25 parts of water glass with a silicon content of 26 wt% in 22 parts of deionized water. Dilute 4.8 parts of concentrated sulfuric acid with a concentration of 98 wt% in 19.2 parts of deionized water. Then slowly add the diluted water glass to the diluted sulfuric acid, the dropping time is 30 minutes, and the stirring speed is 200rpm / min. After the dropwise addition is completed, 42 parts of ammonia water with a mass concentration of 1% is slowly added to the silica sol and stirred to make the sol pH 7 for gelation. Then heat the gel to 70°C for aging, the aging time is 12 hours, and obtain silica gel.
[0025] Step 2, the aged silica gel is crushed, 50 parts of hydrochloric acid with a concentration of 30 wt% and 200 parts of hexamethyldisiloxane are added to hydrophobically modify the gel, the modification temperature is 65 ° C, the modification time is 4h, and the stirring speed is 300rpm / min. After the modification is completed and cooled, the modified waste liquid of the lower layer is released, and then the gel solution of the upper layer is filtered to recover the solvent. 200 parts of hexamethyldisiloxane are added to the filtered gel for stirring and cleaning, the cleaning time is 0.5h, the stirring speed during cleaning is 200rpm / min, and after cleaning, it is left to stand for 1h, and then filtered. The filtered gel is dried at a drying temperature of 120 ° C and a drying time of 3h to obtain silica aerogel powder.
[0026] Step 3: Dissolve 0.05 parts of silica aerogel powder in 100 parts of anhydrous ethanol by weight, then soak the dried wood board in the silica aerogel powder ethanol solution, evacuate the soaking container to 0.01 MPa, and then soak for 2 hours. Dry the soaked wood board in an oven at 100° C. for 2 hours to obtain the final product.
[0027] Test Application Test 1: The final product was cut into 1cm thick and 20*20cm boards, and the thermal conductivity at room temperature was measured by the flat plate heat flow method. The thermal conductivity of the final product at room temperature was 0.064W / (m·K). From the thermal conductivity of the final product, it can be seen that the silica aerogel powder has a good effect of reducing the thermal conductivity of wood. At the same time, it can be seen that the modification degree and performance of the silica aerogel powder will greatly affect the thermal insulation performance of the final product.
[0028] Test 2: The final product was cut into boards with a thickness of 1 cm and a size of 30*15 cm, and its hydrophobicity was tested with a hydrophobicity meter. The hydrophobicity of the final product was 98.44%. From the change in the hydrophobicity of the final product, it can be seen that the silica aerogel powder has a good enhancing effect on the hydrophobicity of wood. At the same time, it can be known that the modification degree and performance of the silica aerogel powder will greatly affect the hydrophobicity of the final product.
[0029] Test three, the final product was cut into 1cm thick and 16*5cm boards, and its tensile strength was tested with an electronic universal testing machine. The tensile strength of the final product was 69.3MPa. We can conclude that silica aerogel powder can significantly improve the tensile strength of wood.
[0030] Example 3 A method for preparing a heat-insulating and hydrophobic wooden board, the specific steps are as follows: Step 1, by weight, dilute 25 parts of water glass with a silicon content of 26 wt% in 22 parts of deionized water. Dilute 4.8 parts of concentrated sulfuric acid with a concentration of 98 wt% in 19.2 parts of deionized water. Then slowly add the diluted water glass to the diluted sulfuric acid, the dropping time is 30 minutes, and the stirring speed is 200rpm / min. After the dropwise addition is completed, 42 parts of ammonia water with a mass concentration of 1% is slowly added to the silica sol and stirred to make the sol pH 7 for gelation. Then heat the gel to 70°C for aging, the aging time is 12 hours, and obtain silica gel.
[0031] Step 2, the aged silica gel is crushed, 50 parts of hydrochloric acid with a concentration of 30 wt% and 200 parts of hexamethyldisiloxane are added to hydrophobically modify the gel, the modification temperature is 65 ° C, the modification time is 4h, and the stirring speed is 300rpm / min. After the modification is completed and cooled, the modified waste liquid of the lower layer is released, and then the gel solution of the upper layer is filtered to recover the solvent. 200 parts of hexamethyldisiloxane are added to the filtered gel for stirring and cleaning, the cleaning time is 0.5h, the stirring speed during cleaning is 200rpm / min, and after cleaning, it is left to stand for 1h, and then filtered. The filtered gel is dried at a drying temperature of 120 ° C and a drying time of 3h to obtain silica aerogel powder.
[0032] Step 3: Dissolve 0.1 parts of silica aerogel powder in 100 parts of anhydrous ethanol, then soak the dried wood board in the silica aerogel powder ethanol solution, evacuate the soaking container to 0.01 MPa, and then soak for 3 hours. Dry the soaked wood board in an oven at 100° C. for 2 hours to obtain the final product.
[0033] Test Application Test 1: The final product was cut into 1cm thick and 20*20cm plates, and the thermal conductivity at room temperature was measured by the flat plate heat flow method. The thermal conductivity of the final product at room temperature was 0.052W / (m·K). It can be seen that increasing the content of silica aerogel powder during dipping will further improve the thermal insulation performance of our final product.
[0034] Test 2: The final product was cut into 1cm thick and 30*15cm boards, and its hydrophobicity was tested with a hydrophobicity meter. The hydrophobicity of the final product was 99.07%. It can be seen that increasing the content of silica aerogel powder during dipping will further improve the hydrophobic properties of our final product.
[0035] Test three, the final product was cut into 1cm thick and 16*5cm plates, and its tensile strength was tested with an electronic universal testing machine. The tensile strength of the final product was 73.5MPa. It can be seen that increasing the content of silica aerogel powder during dipping will further improve the tensile strength of our final product.
[0036] Example 4 A method for preparing a heat-insulating and hydrophobic wooden board, the specific steps are as follows: Step 1, by weight, dilute 25 parts of water glass with a silicon content of 26 wt% in 22 parts of deionized water. Dilute 4.8 parts of concentrated sulfuric acid with a concentration of 98 wt% in 19.2 parts of deionized water. Then slowly add the diluted water glass to the diluted sulfuric acid, the dropping time is 30 minutes, and the stirring speed is 200rpm / min. After the dropwise addition is completed, 42 parts of ammonia water with a mass concentration of 1% is slowly added to the silica sol and stirred to make the sol pH 7 for gelation. Then heat the gel to 70°C for aging, the aging time is 12 hours, and obtain silica gel.
[0037] Step 2, the aged silica gel is crushed, 50 parts of hydrochloric acid with a concentration of 30 wt% and 200 parts of hexamethyldisiloxane are added to hydrophobically modify the gel, the modification temperature is 65 ° C, the modification time is 4h, and the stirring speed is 300rpm / min. After the modification is completed and cooled, the modified waste liquid of the lower layer is released, and then the gel solution of the upper layer is filtered to recover the solvent. 200 parts of hexamethyldisiloxane are added to the filtered gel for stirring and cleaning, the cleaning time is 0.5h, the stirring speed during cleaning is 200rpm / min, and after cleaning, it is left to stand for 1h, and then filtered. The filtered gel is dried at a drying temperature of 120 ° C and a drying time of 3h to obtain silica aerogel powder.
[0038] Step three, dissolve 0.1 parts of silica aerogel powder in 100 parts of anhydrous ethanol, then soak the dried wooden board in the silica aerogel powder ethanol solution, evacuate the immersion container to 0.01 MPa, and then immerse for 3 hours. Dry the impregnated wooden board in an oven at 100°C for 2 hours. Immerse the dried wooden board again in the silica aerogel powder ethanol solution, evacuate the immersion container to 0.01 MPa, and then immerse for 3 hours. The wooden board immersion-drying process is completely cycled three times to obtain the final product.
[0039] Test Application Test 1: The final product was cut into 1cm thick and 20*20cm plates, and the thermal conductivity at room temperature was measured by the flat plate heat flow method. The thermal conductivity of the final product at room temperature was 0.046W / (m·K). It can be seen that increasing the number of impregnations of silica aerogel powder will further improve the thermal insulation performance of our final product.
[0040] Test 2: The final product was cut into 1cm thick and 30*15cm boards, and its hydrophobicity was tested with a hydrophobicity meter. The hydrophobicity of the final product was 99.33%. It can be seen that increasing the number of impregnations of the silica aerogel powder will further improve the hydrophobic properties of our final product.
[0041] Test three, the final product was cut into 1cm thick and 16*5cm plates, and its tensile strength was tested with an electronic universal testing machine. The tensile strength of the final product was 71.8MPa. It can be seen that after the product is impregnated with a sufficient amount of silica aerogel powder, its tensile strength tends to be stable and no longer changes with the number of cycles.
[0042] Example 5 A method for preparing a heat-insulating and hydrophobic wooden board, the specific steps are as follows: Step 1, by weight, dilute 25 parts of water glass with a silicon content of 26 wt% in 22 parts of deionized water. Dilute 4.8 parts of concentrated sulfuric acid with a concentration of 98 wt% in 19.2 parts of deionized water. Then slowly add the diluted water glass to the diluted sulfuric acid, the dropping time is 30 minutes, and the stirring speed is 200rpm / min. After the dropwise addition is completed, 42 parts of ammonia water with a mass concentration of 1% is slowly added to the silica sol and stirred to make the sol pH 7 for gelation. Then heat the gel to 70°C for aging, the aging time is 12 hours, and obtain silica gel.
[0043] Step 2, the aged silica gel is crushed, 50 parts of hydrochloric acid with a concentration of 30 wt% and 200 parts of hexamethyldisiloxane are added to hydrophobically modify the gel, the modification temperature is 65 ° C, the modification time is 4h, and the stirring speed is 300rpm / min. After the modification is completed and cooled, the modified waste liquid of the lower layer is released, and then the gel solution of the upper layer is filtered to recover the solvent. 200 parts of hexamethyldisiloxane are added to the filtered gel for stirring and cleaning, the cleaning time is 0.5h, the stirring speed during cleaning is 200rpm / min, and after cleaning, it is left to stand for 1h, and then filtered. The filtered gel is dried at a drying temperature of 120 ° C and a drying time of 3h to obtain silica aerogel powder.
[0044] Step three, dissolve 0.1 parts of silica aerogel powder in 100 parts of anhydrous ethanol, then soak the dried wooden board in the silica aerogel powder ethanol solution, evacuate the immersion container to 0.01 MPa, and then immerse for 3 hours. Dry the impregnated wooden board in an oven at 100°C for 2 hours. Immerse the dried wooden board again in the silica aerogel powder ethanol solution, evacuate the immersion container to 0.01 MPa, and then immerse for 3 hours. The wooden board immersion-drying process is completely cycled five times to obtain the final product.
[0045] Test Application Test 1: The final product was cut into plates with a thickness of 1 cm and a size of 20*20 cm, and its room-temperature thermal conductivity was measured using the flat plate heat flow method. The room-temperature thermal conductivity of the final product was 0.047 W / (m·K). It can be seen that the room-temperature thermal conductivity of the product has tended to be stable during the three impregnation-drying processes, and its thermal insulation performance has not changed much after five cycles.
[0046] Test 2: The final product was cut into 1cm thick and 30*15cm boards, and its hydrophobicity was tested with a hydrophobicity meter. The hydrophobicity of the final product was 99.41%. It can be seen that the hydrophobicity of the product has stabilized during the three immersion-drying processes, and its hydrophobic performance has not changed much after five cycles.
[0047] Test three, the final product was cut into 1cm thick and 16*5cm boards, and its tensile strength was tested with an electronic universal testing machine. The tensile strength of the final product was 70.2MPa. It can be seen that after the wood is impregnated with a sufficient amount of silica aerogel powder, its tensile strength tends to be stable and no longer changes with the number of cycles.
[0048] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing heat-insulating and hydrophobic wood, characterized in that: The following steps are involved: S1, using a silicon source and an acid as raw materials, mixing to prepare a silica sol, then adding an alkaline solution to prepare a gel and aging; S2, the aged gel is crushed, hexamethyldisiloxane and hydrochloric acid are added for hydrophobic modification, and after modification, it is cooled and allowed to stand, the modified waste liquid at the lower layer is discharged, the gel solution at the upper layer is filtered, and dried to obtain modified silica aerogel powder; S3, adding the modified silica aerogel powder obtained in S2 into ethanol and mixing evenly, adding dry wood for vacuum impregnation, and drying after the impregnation to obtain heat-insulating and hydrophobic wood.
2. The method according to claim 1, characterized in that: The silicon source in S1 is water glass with a silicon content of 20-30%; the acid is concentrated sulfuric acid with a concentration of 80-98%; water needs to be added during the mixing process, the mass ratio of water glass to water is 1-5:1-5, and the mass ratio of concentrated sulfuric acid to water is 1-5:1-10; after the silicon source, acid and water are mixed, a sol is obtained by dropping and stirring, the dropping time is 10-60 min, and the stirring speed is 100-1000 rpm / min.
3. The method according to claim 1, characterized in that: The alkaline solution in S1 is ammonia water with a concentration of 1-10%, and the mass ratio of sol to ammonia water is 1-10:1-5; the pH of the sol is adjusted to 3-8 by ammonia water; the temperature of gel heating aging is 40-80°C; and the aging time is 1-24h.
4. The method according to claim 1, characterized in that: The mass ratio of hydrochloric acid, hexamethyldisiloxane and gel in S2 is 1~5:1~10:1~5; the concentration of hydrochloric acid is 25-35%; the temperature for hydrophobic modification of the gel is 40~80°C; the stirring speed is 100~1000rpm / min; and the modification time is 1~12h.
5. The method according to claim 1, characterized in that: The filter cake after filtering the gel solution in the upper layer of S2 is mixed and washed with hexamethyldisiloxane, filtered again, and then dried.
6. The method according to claim 1, characterized in that: The drying temperature of the gel in S2 is 70~150℃.
7. The method according to claim 1, characterized in that: The mass ratio of modified silica aerogel powder to ethanol in S3 is 0.001~1:1~5.
8. The method according to claim 7, characterized in that: The impregnation vacuum pressure in S3 is 0.01~0.1MPa; the impregnation time is 1~5h; the drying temperature of the wood board is 80~150℃; the drying time is 1~5h.
9. The method according to claim 1, characterized in that: The dipping and drying steps in S3 are repeated 1 to 5 times.
10. The heat-insulating and hydrophobic wood prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Production method of super-hydrophobic wood
CN111185977A
Cited By
Waterproof fiber composite board and preparation method thereof
CN121179533A
Waterproof fiber composite board and preparation method thereof
CN121179533B